2012
DOI: 10.1177/1753193412445441
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-operative comorbidities in idiopathic carpal tunnel syndrome: cervical arthritis, basal joint arthritis of the thumb, and trigger digit

Abstract: We retrospectively reviewed 633 hands in 362 patients who had idiopathic carpal tunnel syndrome and underwent carpal tunnel release between 1999 and 2009. Electrophysiological studies and simple radiographs of the wrist, cervical spine, and basal joint of the thumb were routinely checked, and patients were also assessed for the presence of trigger digit or de Quervain's disease before and after surgery. Among 362 patients, cervical arthritis was found in 253 patients (70%), and C5-C6 arthritis was the most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 23 publications
2
21
0
4
Order By: Relevance
“…The development of TF in patients undergoing surgical treatment of CTS has been analyzed by various authors [Table 4]. [16171819202122232425262728] The reported incidence of TF after CTR is about 10%–20%, which is almost identical to the results of our study, and CTR has been attributed to acceleration of the development of TF in various studies.…”
Section: Reports Of Trigger Finger Occurrence After Carpal Tunnel Relsupporting
confidence: 87%
“…The development of TF in patients undergoing surgical treatment of CTS has been analyzed by various authors [Table 4]. [16171819202122232425262728] The reported incidence of TF after CTR is about 10%–20%, which is almost identical to the results of our study, and CTR has been attributed to acceleration of the development of TF in various studies.…”
Section: Reports Of Trigger Finger Occurrence After Carpal Tunnel Relsupporting
confidence: 87%
“…We found a total of 224 papers, but only seven relevant studies emerged from the first pass and just four after the second pass [4][5][6][7] (Table 1). Unfortunately, none of the studies had a valid control group, and all raised questions related to the statistical analysis (confounding factors?…”
Section: Dear Editorsmentioning
confidence: 96%
“…However, a relationship is possible, related to anatomy and biomechanics modifications after CTR (e.g. possible volar migration of the flexor tendons) [7,8] and/or to a coexisting disorder (with the same etiology) [4,6,9,10]. Checking for TF or pain at the A1 pulley is recommended before CTR.…”
Section: Dear Editorsmentioning
confidence: 97%
“…Carpal tunnel syndrome (CTS) and stenosing tenosynovitis or trigger finger (TF) are common. TF is associated with CTS (Ferree et al, 2014; Harada et al, 2005; Hayashi et al, 2005; Hombal and Owen, 1970; Kim et al, 2013; Kumar et al, 2009) and occurs more frequently after carpal tunnel release (CTR) (Harada et al, 2005; Hayashi et al, 2005; Hombal and Owen, 1970; King et al, 2013). Stahl et al (1997) reported that the lifetime incidence of trigger finger was 2.2% in nondiabetic adults older than 30 years and up to 10% in patients with insulin-dependent diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of TF associated with CTS has been reported to be 10.2% to 21% (Assmus, 2000; Hayashi et al, 2005; Kumar et al, 2009). The incidence of TF after CTR has been reported to be between 6.3% and 21.9% (Goshtasby et al, 2010; Harada et al, 2005; Hayashi et al, 2005; Hombal and Owen, 1970; Kim et al, 2013; King et al, 2013). Some studies have investigated the significance of variable risk factors predisposing patients to developing TF after CTR (Goshtasby et al, 2010; Harada et al, 2005; Hayashi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%